Effective Strategies using Digital Literacy for Empowering Critical Thinking in Higher Education - Manggopa, Hiskia Kamang; Kumampung, Deislie R. Henrieta (JR Education, 2023)
In the digital era, digital literacy skills have become important in equipping students with the skills to participate actively in an increasingly connected and complex society. Likewise, critical thinking skills are essential in helping students develop deep understanding, good analysis, and evaluation of the information they encounter. This study aims to investigate effective strategies for using digital literacy to empower critical thinking skills in higher education. This research will adopt a qualitative approach using the case study method in several higher education institutions. Data will be collected through in-depth interviews, observation, and document analysis related to digital literacy strategies in the learning environment. Next, the data will be analyzed using a content analysis approach to identify which strategies most effectively empower students' critical thinking skills. It is hoped that the results of this study will provide in-depth insight into how digital literacy can be properly integrated into the higher education curriculum to stimulate students' critical thinking skills. The implication of this research is to provide practical guidance to educators, lecturers, and decision-makers in higher education institutions to design learning strategies that support the development of digital literacy and critical thinking. In addition, this research can also contribute to further research in the field of digital literacy and higher education. With a stronger focus on incorporating digital technologies in higher education, it is hoped that this research will provide valuable directions for the development of relevant and innovative curricula, which in turn will help produce graduates who are not only technically proficient but also able to think critically in facing complex modern world challenges.